Design and implementation data classification using fuzzy c-means based on hybrid clustering technique - patidar, Nitin; Patidar, Kushboo (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
The management and analysis of big data has been recognized as one of the majority significant promising requirements in recent years. This is because of the pure volume and growing complexity of data creature created or composed. Existing clustering algorithms cannot grip big data, and consequently, scalable solutions are essential. The experimental analysis will be accepted out to assess the practicability of the scalable Possibilistic Fuzzy CMeans (PFCM) clustering technique and partial Fuzzy C-Means (PFCM) clustering technique.. Two-stage and twophase fuzzy C-means (FCM) algorithms have been report. In this paper, to exhibit that the Hybrid FCM clustering algorithm (HFCM) can be enhanced by the utilization of static and dynamic single-pass incremental FCM measures. Proposed technique finds upper head over existing technique in terms of accuracy, classification error entitlement and time. To observed that multistage clustering can speed up convergence and advance clustering superiority.